Обзор и анализ моделей и методов юзабилити, применяемых в процессе разработки и оценки интерфейса ПО - Груздо, И. В. (ХНУРЕ, 2020)
This paper studies the usability models and methods used in the development and evaluation of a software interface. Based on the results of the analysis, the need for the integrated use of mathematical and methodological support for the analysis of software interfaces is shown.